IMPLEMENTASI KEBIJAKAN STANDAR PELAYANAN MINIMAL PENDIDIKAN SEKOLAH MENENGAH PERTAMA DI KABUPATEN BANYUMAS - Lupita Ariantika Sari (Majalah Ilmiah Dinamika Administrasi (MIDA), 2022)
This research entitled "Implementation of Minimum Service Standards for Junior High School Education in Banyumas Regency". This research based result the achievement of MSS Junior High School in Banyumas Regency which is still low, especially the availability of facilities and infrastructure and the availability. Therefore, the need for research on the implementation of MSS policy of junior high school education based on the implementation theory of Van Meter and Van Horn. The purpose of this research is to analyze and describe how the implementation of policy of minimum service standard of junior high school in Banyumas Regency. This research used qualitative research method. The technique of selecting informant used purposive sampling technique. Methods of data collection used interview, observation, and documentation. The result obtained shows that implementation of SPM education has not been implemented maximally according to the theory Implementation of Van Meter and Van Horn policy. This is evidenced by the unavailability of standard and target of MSS policy and the absence of SOP made by Banyumas District Education Office. human resources in terms of competence less support, financial resources usage not maximal, least communications, bad attitude executor, and least support from external environment.